The challenges and ethical dilemmas of a military medical officer serving with a peacekeeping operation in regard to the medical care of the local population. Issue 10 (30th September 2005) - Tobin, J
Abstract : Medical Officers serving with their national contingents in peacekeeping operations are faced with difficult ethical decisions in regard to their obligations to the local civilian population. Such populations may be under-resourced in regard to medical care, and vulnerable to abuse and exploitation. Though the medical officer may support the local medical services, he/she should never undermine these resources. Adopting a human rights approach and observing the requirements of ethical medicine, aids the doctor in prioritising his/her duties. At times there may be conflict with one's own military superiors. It is wise to discuss potential difficulties prior to setting out on the mission. Human rights abuses cannot be ignored. The medical officer has a duty to do his/her best to report their observations so as to prevent abuse or to bring it to an end.